The role of nuclear factor of activated T cells during phorbol myristate acetate-induced cardiac differentiation of mesenchymal stem cells - Seo, Hyang-Hee (Stem Cell Res Ther, 2016)
BACKGROUND: We previously reported that phorbol 12-myristate 13-acetate (PMA) treatment can induce the cardiac differentiation of mesenchymal stem cells (MSCs). In the present study, we investigated how PMA induces cardiac differentiation of MSCs, focusing on its effect on the transcription factors responsible for increased cardiac marker gene expression. METHODS: Human MSCs (hMSCs) were treated with 1 μM PMA for 9 days. The expression of MSC markers and cardiac markers in the PMA-treated hMSC, as well as the nuclear translocation of transcription factors, nuclear factor of activated T cells (NFAT), and myogenic differentiation 1 (MyoD), was examined. Transcriptional activity of NFAT was examined by utilizing a green fluorescent protein (GFP) vector containing NFAT motif of human interleukin-2 promoter. The effect of PMA on the expression of key cell cycle regulators was examined. RESULTS: PMA induces the transcriptional activity of NFAT and MyoD, which have been associated with increased expression of cardiac troponin T (cTnT) and myosin heavy chain (MHC), respectively. Our data suggested that protein kinase C (PKC) mediates the effect of PMA on NFAT activation. Furthermore, PMA treatment increased cell-cycle regulator p27(kip1) expression, suggesting that PMA triggers the cardiac differentiation program in MSCs by regulating key transcription factors and cell cycle regulators. CONCLUSIONS: The results of this study demonstrate the importance of NFAT activation during PMA-induced MSC differentiation and help us to better understand the underlying mechanisms of small molecule-mediated MSC differentiation so that we can develop a strategy for synthesizing novel and improved differentiation-inducing small molecules. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13287-016-0348-6) contains supplementary material, which is available to authorized users.